Biomarker hydrogen isotope composition (δD) as proxy for Holocene hydroclimatic change and seismic activity in SW Peloponnese, Greece. (26th June 2018) - Norström, Elin; Katrantsiotis, Christos; Finné, Martin; Risberg, Jan; Smittenberg, Rienk H.; Bjursäter, Stefan
ABSTRACT: We present a 6000‐year‐long record tracing hydroclimate changes in SW Greece, based on hydrogen isotope composition of aquatic plant‐derived n ‐C23 alkanes (δDC23 ) in a sediment core from the Messenian plain, Peloponnese. The δDC23 record co‐varies with other eastern Mediterranean records, suggesting relatively wetter conditions c . 6–4.5 ka, followed by progressively drier conditions leading up to maximum aridity c . 2.8 ka. This arid phase was interrupted by a shift in δDC23 between 3.3 and 3.1 ka inferring wetter conditions and/or tentative responses to anthropogenic water regulating activities during the Late Bronze Age. After 2.7 ka, a return to more humid conditions was followed by increased dryness and stronger seasonality contrasts from c . 2.0 ka. The δDC23 record shows three short‐lived excursions (5.7, 5.3, 2.8 ka), where isotope values dropped by >20‰ and immediately stabilized again. The events were paralleled by abrupt increases in sedimentation rates. We hypothesize that the isotopic shifts represent a response to mixing of ground water systems during tectonic events, followed by sealing of seismically derived cracks in the active fault. The outcome of the study is promising for future expansion of isotope‐based proxies on sediments in the region, to reconstruct both hydroclimate and past seismic activity.